Sementes orgânicas : regulamentação, políticas públicas, produção comercial e uso de sementes locais em estabelecimentos certificados - Parra Filho, Antonio Carlos Mendes (2015)
The seed is the first link in the food production chain. In this context, the use of appropriate seeds and seedlings in organic production can be understood as, more than a legal or philosophical question, a technical strategy to better results in organic production. The objectives of this study were: contextualize, analyze and interpret the seed laws, public policies related to local seeds; analyze the standards related to the use of seed in organic production in Brazil; the commercial production of organic seeds in Brazil by the private sector, public sector and third sector; and the use of local seeds by certified establishments. The Brazilian regulations preserved the primary rights of traditional farmers and communities regarding the use and local seed multiplication. Thus, the National Plan for Organic Production and Agroecology (Planapo) gathered some public policies that were based on those rights. Brazilian regulations allowed the use of conventional seeds and seedlings in organic production while there is no supply of organic seeds in the formal market. This is an indicative of the conventionalization process. Commercial production of organic seeds was more significant among third sector organizations linked to family farmers and philosophical currents, which were identified as the pioneers of the organic agriculture movement. Thus, we also see the greatest indexes of local seeds use among organizations of the third sector and family farms.